The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3906/elk-1604-102
|View full text |Cite
|
Sign up to set email alerts
|

Novel control strategy for hybrid renewable energy-based standalone system

Abstract: Abstract:In this paper, novel control strategies are proposed for a hybrid renewable energy system under a standalone environment. The wind unit, solar unit, supercapacitor (SC), and battery are connected to a DC link through power converters. Control methods are proposed to mitigate the limitations of the standalone system. The control method is proposed to maintain constant DC link voltage under different conditions without using a dummy load (i.e. an electrolyzer). The SC and battery are used as storage dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…It is a technique that continues until the local minimum of the nonlinear function is found [17][18]. The LM algorithm, which gives the fastest and most reliable results in feed forward networks, has become a standard technique for nonlinear least squares problems [19][20].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…It is a technique that continues until the local minimum of the nonlinear function is found [17][18]. The LM algorithm, which gives the fastest and most reliable results in feed forward networks, has become a standard technique for nonlinear least squares problems [19][20].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Further, considering the slow dynamic response of BESS, the author further proposes a closed-loop control that extracts the uncompensated error component from the BESS that additionally controls the SCSS duty cycle. Hence, increasing the controllability of DC-voltage regulation under load-generation mismatch conditions even without the need for dump loads [117], nevertheless, the BESS stress is further reduced. This proposed design has been further enhanced to give a PI-fuzzy-based PFS technique [118], for effective reduction of BESS stress and hence achieve faster DC voltage restoration.…”
Section: Demand-generation Power Flow Managementmentioning
confidence: 99%
“…Kulaksiz et al presented a genetic algorithm (GA) method to improve the maximum power point tracing capacity of a photovoltaic system [2]. Sharma et al proposed an optimal power point tracking and control method for a hybrid renewable energy system under an independent environment [3]. Raju et al suggested the application of the improved distributed energy management system and request management of a solar microgrid using a multiagent system coordination method [4].…”
Section: Introductionmentioning
confidence: 99%